MODULATION OF THE MICRO-ENVIRONMENTAL PH AND ITS INFLUENCE ON THE GEL LAYER BEHAVIOR AND RELEASE OF THEOPHYLLINE FROM HYDROPHILIC MATRICES - AIMAN A. OBAIDAT (International Journal of Pharma and Bio Sciences, 2013)
The specific aim of this study was to develop a pH independent controlled release system for the basic drug, theopylline. The release of the drug was investigated in vitro from hydrophilic swellable matrices composed of hydroxyethyl cellulose and Eudragit S-100. The micro-environmental pH of the hydrated gel layer of the matrices was manipulated by the addition of fumaric acid. It is expected that the solubility of theophylline and release form matrices, without controlled micro-environmental pH, will decrease as the matrix tablets travel down the GIT which may lead to incomplete solubility and release of the drug, and hence, low bioavailability. Incorporation of fumaric acid in the matrix formulation was found to control the micro-environmental pH of the hydrated gel layer and resulted in pH independent release of the drug irrespective of the dissolution medium and its pH. Thus, efficient and predictable drug release is expected from such matrices.